The oil pulling miracle : detoxify simply and effectively - Frohn, Birgit, 1967- (Healing Arts Press, 2016)
"Using coconut, sesame, and other oils to heal chronic conditions, strengthen the immune system, and prevent illness. Details the process of oil pulling, including when to do it, how long to swish the oil in your mouth, and other oral care techniques that complement it. Explains the health benefits of 10 different cold-pressed oils, including sesame, coconut, and pumpkin seed, allowing you to choose the best oil for your needs. Includes a step-by-step 7-day detox plan andinformation on additional detox techniques that enhance the benefits of oil pulling. Oil pulling is much more than an oral cleansing method. Originating in the ancient healing systems of Ayurveda and traditional Chinese medicine, where it is well knownthat "disease begins in the mouth," this simple health practice triggers detoxification and healing throughout the entire body. The mouth and tongue are home to bacteria, fungus, and many toxins from the rest of the body. Oil pulling not only cleanses the mouth and tongue, preventing harmful bacteria and toxins from entering the bloodstream, it also triggers enzyme production in the digestive tract, which in turn activates cleansing processes throughout the entire body. Practiced daily, oil pulling leads to better dental and gum health, a stronger immune system, detoxification of major organs including the intestines, lungs, and liver, and healing from many conditions caused by internal toxins and chronic inflammation. In this practical guide, Birgit Frohn details the simple process of oil pulling, including when to do it, how long to swish the oil in your mouth, and other oral care techniques that complement it, such as tongue scraping. She explains the specific health benefits of 10 different cold-pressed oils that can be used in oil pulling, from traditional sesame oil to vitamin-packed pumpkin seed oil to highly popular coconut oil, allowing you to choose the best oil for your needs. She also reveals the vast number of ailments that can be healed and prevented by regular oil pulling practice, including: Acne, Allergies, Canker sores, Arthritis, Eczema, Flu and Colds, Sinus infections and Bronchitis, Cavities and Gingivitis, Headaches and Migraines,Constipation, and many more. Frohn also explores additional detox techniques that enhance the benefits of oil pulling and concludes with a step-by-step 7-day detox plan for those who want to maximize the effects of oil pulling and accelerate their return to better health"--